2019
DOI: 10.1038/s41598-019-49223-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic, but not acute, fatigue predicts self-reported attentional driving errors in mothers attending infant children

Abstract: Mothers attending infant children usually experience high levels of fatigue, and fatigue has been shown to be related to car crashes through attentional errors, among other causes. The current study investigates the effects of fatigue on the attentional errors while driving of women attending infant children. A sample of 112 women—67 attending infant children and 45 not attending—filled out self-report questionnaires assessing acute fatigue, chronic fatigue, and attention-related driving errors. A mediational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…A key metric for assessing fatigue-related driving is the performance of the task itself, including attention related errors, lane deviation, and harsh braking. Despite the importance of these metrics, just three studies included an assessment of driver performance, though measurement strategies vary widely and make comparison difficult (Harpham et al 2015;Sánchez-García et al, 2019;Sedgley et al, 2012). In addition, driving performance data collected in the 6-8 weeks post-birth (Harpham et al 2015;Sedgley et al, 2012), may be confounded by physical recovery post-birth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A key metric for assessing fatigue-related driving is the performance of the task itself, including attention related errors, lane deviation, and harsh braking. Despite the importance of these metrics, just three studies included an assessment of driver performance, though measurement strategies vary widely and make comparison difficult (Harpham et al 2015;Sánchez-García et al, 2019;Sedgley et al, 2012). In addition, driving performance data collected in the 6-8 weeks post-birth (Harpham et al 2015;Sedgley et al, 2012), may be confounded by physical recovery post-birth.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that those who had reported a crash or near miss reported poorer sleep outcomes, in addition to greater rates of having fallen asleep while driving in the past (Malish & Arastu, 2016). Another study showed that 6% of women attending infant children (i.e., caregivers of children) reported having had a 'driving incident' since the birth of their childthough the definition of 'driving incident' is unclear (Sánchez-García et al, 2019). Study 2 of the Mackenzie (2016b) thesis asked 137 new mothers to report how frequently they had experienced a range of impairment related incidents since the birth of their child.…”
Section: Motor Vehicle Crashes Near Misses and Incidentsmentioning
confidence: 90%
See 2 more Smart Citations
“…One important issue that must be addressed is the duration of the fatigue suffered by mothers during the first few months of raising the infant. This fatigue is, in part, a product of the lack of sleep associated with the infant’s feeding, care and sleep rhythm—since the newborn’s sleep rhythms are not yet well-established and their needs for food, affection, cleanliness and activity are not synchronized with the rhythms of the parents—and also with other factors that can cause the fatigue to become chronic [ 20 ] and evolve into other, more serious problems such as chronic stress or depression [ 21 , 22 ]. Thus, although mothers’ may sleep for longer once the infant matures, the pressure of the abovementioned tasks—which had been postponed because they were regarded as less urgent—is still present, delaying the recovery from fatigue beyond the first few months.…”
Section: Introductionmentioning
confidence: 99%